1998
DOI: 10.1046/j.1365-246x.1998.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Sea-level change, glacial rebound and mantle viscosity fornorthern Europe

Abstract: Northwestern Europe remains a key region for testing models of glacial isostasy because of the good geological record of crustal response to the glacial unloading since the time of the Last Glacial Maximum. Models for this rebound and associated sealevel change require a detailed knowledge of the ice-sheet geometry, including the ice thickness through time. Existing ice-sheet reconstructions are strongly model-dependent, and inversions of sea-level data for the mantle response may be a function of the model as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
471
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 552 publications
(501 citation statements)
references
References 60 publications
28
471
1
1
Order By: Relevance
“…Similar findings from the Skagerrak support this interpretation. There, the small coral reefs are under the influence of the isostatic balance of the glacial rebound of Scandinavia lifting the lithosphere and bringing the corals continuously under the influence of the low-saline Baltic water (e.g., Lambeck et al, 1998). Foraminiferal assemblages in the coral facies have only a small contribution of D. coronata, which indicates that the abundance of this species mirrors similar ecological requirements as the corals.…”
Section: Maya Mud Volcanomentioning
confidence: 99%
“…Similar findings from the Skagerrak support this interpretation. There, the small coral reefs are under the influence of the isostatic balance of the glacial rebound of Scandinavia lifting the lithosphere and bringing the corals continuously under the influence of the low-saline Baltic water (e.g., Lambeck et al, 1998). Foraminiferal assemblages in the coral facies have only a small contribution of D. coronata, which indicates that the abundance of this species mirrors similar ecological requirements as the corals.…”
Section: Maya Mud Volcanomentioning
confidence: 99%
“…Fjeldskaar 1994;Lambeck et al 1998;Milne et al 2001;Steffen and Kaufmann 2005). They also inform us on vertical land motion-an important component of present-day RSL change for Norway.…”
Section: Present-day Vertical Land Motion In Norwaymentioning
confidence: 95%
“…The ice model is made of two parts: The Fennoscandian and Barents Sea ice sheets are represented by the model of Lambeck et al (1998), which has been shown to provide good fit to paleo sea level data from the region. For other areas of the globe, we use the ICE-3G ice sheet reconstruction of Tushingham and Peltier (1991).…”
Section: Glacial Isostatic Adjustment Modelingmentioning
confidence: 99%
See 2 more Smart Citations